Analysis of the Determinants Influencing Treatment Adherence Among Hypertension Patients in South Sorong Regency - Salkamal, Salkamal; Adam, Arlin; Iskandar, Muhammad Ishaq; ledia, Ida; Zamli, Zamli (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Hypertension is a major risk factor for cardiovascular diseases, driven by lifestyle modernization and its high prevalence. Addressing treatment adherence is crucial for effective management. Objective: This study aimed to analyze the determinants influencing treatment adherence among hypertension patients in South Sorong Regency, with a specific focus on family support. Methods: A quantitative research approach was conducted in South Sorong Regency from May to June 2024. Data were collected through structured questionnaires and analyzed to assess the influence of various factors on treatment adherence. Results: The findings revealed that family support significantly influenced treatment adherence in hypertension patients. In contrast, knowledge, perception, service delivery quality, and patient satisfaction did not show a significant effect on adherence. Conclusion: Family support plays a critical role in enhancing treatment adherence among hypertension patients in South Sorong Regency. To improve adherence, it is recommended to implement family education through counseling at community health centers (puskesmas) and social media, conduct behavior change campaigns, provide family counseling, train health workers to improve service delivery, and strengthen monitoring and evaluation mechanisms for treatment adherence.